2017
DOI: 10.1128/genomea.01213-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Streptococcus thermophilus Strain B59671, Which Naturally Produces the Broad-Spectrum Bacteriocin Thermophilin 110

Abstract: Streptococcus thermophilus strain B59671 is a Gram-positive lactic acid bacterium that naturally produces a broad-spectrum bacteriocin, thermophilin 110, and is capable of producing gamma-aminobutyric acid (GABA). The complete genome sequence for this strain contains 1,821,173 nucleotides, 1,936 predicted genes, and an average G+C content of 39.1%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…For example, the gadB-gadC genes are flanked by transposases elements in S. thermophilus. In S. thermophilus strains ACA-DC 2, B59671, and TH1435, S-ribosylhomocysteine lyase and ribonuclease Y locate, respectively, upstream and downstream of the gadB-gadC operon [47][48][49]. However, for strains ND03 and APC151, DUF1310 family protein and ABC transporter ATP-binding protein locate downstream of gadB-gadC [50,51].…”
Section: Gad System Of Labmentioning
confidence: 99%
“…For example, the gadB-gadC genes are flanked by transposases elements in S. thermophilus. In S. thermophilus strains ACA-DC 2, B59671, and TH1435, S-ribosylhomocysteine lyase and ribonuclease Y locate, respectively, upstream and downstream of the gadB-gadC operon [47][48][49]. However, for strains ND03 and APC151, DUF1310 family protein and ABC transporter ATP-binding protein locate downstream of gadB-gadC [50,51].…”
Section: Gad System Of Labmentioning
confidence: 99%
“…For example, the locus of a class II bacteriocin-like peptide (blp) was experimentally studied in strains CNRZ1066, LMG 18311, and LMD-9 and it was concluded that it is only functional in the last strain (Hols et al, 2005). In strain B59671, GI 5 carries genes of the blp gene cluster involved in the production of the bacteriocin thermophilin 110 (Renye et al, 2017). Finally, in GI 6 of strain GABA we found a locus containing several genes coding for leader peptides (including mutacin IV, BlpU, and bovicin 255), but transport or immunity proteins seem to be inactive or absent ( Supplementary Table S12A).…”
Section: Genomic Islandsmentioning
confidence: 99%
“…Similar to other S. thermophilus strains (6, 13), the ST109 genome contained 13.5% nonfunctional genes; however, ST106 possessed 323 pseudogenes, corresponding to 16.8% of the predicted coding sequences. Previous studies showed that thermophilin 109 was naturally produced and may be encoded within the blp gene cluster (4, 7).…”
Section: Announcementmentioning
confidence: 74%
“…The blp gene cluster has been characterized for S. thermophilus strains LMD-9 (3), ST106, and ST118 (4), where bacteriocin production was induced with a recombinant or synthetic quorum sensing peptide, BlpC-30, and for strain B59671 (5, 6), where production occurs naturally.…”
Section: Announcementmentioning
confidence: 99%